2010
DOI: 10.1063/1.3275704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na nonstoichiometry in (Bi0.5Na0.5+x)TiO3 ceramics

Abstract: Effects of Na nonstoichiometry in (Bi0.5Na0.5+x)TiO3 ceramics were investigated in the range of x=(−5)−(+1) mol % of Na0.5. A rhombohedral perovskite structure was maintained at all compositions with no secondary phases. Grain size decreased with Na nonstoichiometry. Piezoelectric coefficient (d33) increased from 74 pC/N at x=0 up to 91 pC/N at x=−3.5 then dropped with further Na deficiency. Depolarization temperature (Td), on the other hand, decreased from 190 °C at x=0 down to 112 °C at x=−3.5 then increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(61 citation statements)
references
References 24 publications
5
48
0
Order By: Relevance
“…As noted, even in this partial phase diagram, at least four additional Bi-Na-Ti-based oxide compounds including a cubic pyrochlore phase as well as five more other oxide compounds exist as stable phases other than Bi 1/2 Na 1/2 TiO 3 , making the detection of a proper isoplethal path highly challenging. In addition, the task at hand is aggravated by the fact that the functional and structural properties of BNT-based system are highly sensitive to stoichiometry [218][219][220][221], which is even harder to control during the fabrication of single crystals. One potentially promising approach to solve this issue may be to utilize solid-state single crystal fabrication method [193,198,206,222], where at least the composition of the final product is reliable.…”
Section: Perspectivesmentioning
confidence: 99%
“…As noted, even in this partial phase diagram, at least four additional Bi-Na-Ti-based oxide compounds including a cubic pyrochlore phase as well as five more other oxide compounds exist as stable phases other than Bi 1/2 Na 1/2 TiO 3 , making the detection of a proper isoplethal path highly challenging. In addition, the task at hand is aggravated by the fact that the functional and structural properties of BNT-based system are highly sensitive to stoichiometry [218][219][220][221], which is even harder to control during the fabrication of single crystals. One potentially promising approach to solve this issue may be to utilize solid-state single crystal fabrication method [193,198,206,222], where at least the composition of the final product is reliable.…”
Section: Perspectivesmentioning
confidence: 99%
“…Sung et al [18,19] have reported that lattice distortion (90-a) is the key factor for variation in d 33 . Also Hiruma et al [12] have considered that small lattice distortion (90-a) leads to increased piezoelectric constant.…”
Section: Resultsmentioning
confidence: 98%
“…T d , on the contrary, was as low as 127 C at y ¼ À3.5 mol% in Na-deficient compositions and higher in compositions with excessive Na. An inversely proportional relation between d 33 and T d induced by either Bi or Na nonstoichiometry became obvious and was attributed to lattice distortions in the case of Na nonstoichiometry [52]. From these results, it is clear that Bi and Na nonstoichiometry affected piezoelectric and dielectric properties in an opposite way.…”
Section: Nonstoichiometry By Means Of A-site Intrinsicmentioning
confidence: 88%
“…The peaks correspond to the rhombohedral BNT phase, but no secondary phase peak was observed within the samples tested for deficient to excessive compositions of Bi or Na. These XRD patterns were further analyzed to calculate variations in lattice parameters, and lattice distortion turned out to be a key factor, affecting both d 33 and T d [51][52][53].…”
Section: Nonstoichiometry By Means Of A-site Intrinsicmentioning
confidence: 99%